2011
DOI: 10.1002/ejlt.201100142
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative properties of phenolic acids and interaction with endogenous minor components during frying

Abstract: The ability of selected phenolic acids to improve the frying performance of canola oil was evaluated in a frying test. The frying performance of the oil was assessed by analysis of total polar components (TPC), level of 4-hydroxynonenal (HNE), and the rate of formation of volatile carbonyl compounds (VCC). All the tested phenolic acids; ferulic acid (FA), caffeic acid (CA), dihydrocaffeic acid (HCA), gallic acid (GA), and vanillic acid (VA) significantly increased the frying performance of canola oil triacylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The result was based on a single concentration treatment (200 ppm, w/v) during very short time frying process (30, 60, and 90 min only) with only one type of vegetable oil (corn oil). The effect of gallic acid at 500 ppm on the oxidative changes (polar compounds, volatile compounds, and hydroxynonenal) of purified canola oil triacylglycerol during short period (120 min) heating at 185 o C has also been reported (21). The result was also based on the single concentration (500 ppm) of gallic acid on the thermal oxidation of purified canola triacylglycerols.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The result was based on a single concentration treatment (200 ppm, w/v) during very short time frying process (30, 60, and 90 min only) with only one type of vegetable oil (corn oil). The effect of gallic acid at 500 ppm on the oxidative changes (polar compounds, volatile compounds, and hydroxynonenal) of purified canola oil triacylglycerol during short period (120 min) heating at 185 o C has also been reported (21). The result was also based on the single concentration (500 ppm) of gallic acid on the thermal oxidation of purified canola triacylglycerols.…”
Section: Introductionmentioning
confidence: 91%
“…The information on the protective activity of gallic acid on the thermal oxidation of vegetable oils at frying temperature was surprisingly scarce. There was only a few reports on the protective activity of gallic acid on the thermal oxidation of vegetable oils (20,21). However, the comparative protective activity of gallic acid with the synthetic antioxidants on the thermal oxidation of vegetable oils has not been reported previously.…”
mentioning
confidence: 99%
“…Besides this antioxidant degradation phenomenon, there is also the possibility of composing new, in situ secondary antioxidants as a consequence of some physico‐chemical reactions involving antioxidants, food materials (starch and protein), and lipid degradation products during frying. For instance, it was recently observed that the reactions between endogenous phytosterols and added phenolic acids during frying can create a synergistic relationship through in situ formation of steryl ferulates, a secondary antioxidant . Indeed, the influence of components' molar ratios and other conditions necessary for such in situ synthesis requires further investigations.…”
Section: Natural Antioxidantsmentioning
confidence: 99%